2020
DOI: 10.3390/v12090927
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epidermal Growth Factor Receptor Signaling Pathway during Bovine Herpesvirus 1 Productive Infection in Cell Culture

Abstract: Accumulating studies have shown that the epidermal growth factor receptor (EGFR) signaling pathway plays an essential role in mediating cellular entry of numerous viruses. In this study, we report that bovine herpesvirus 1 (BoHV-1) productive infection in both the human lung carcinoma cell line A549 and bovine kidney (MDBK) cells leads to activation of EGFR, as demonstrated by the increased phosphorylation of EGFR at Tyr1068 (Y1068), which in turn plays important roles in virus infection. A time-of-addition as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Since EGFR does not affect JEV attachment and entry in hBMECs, how does EGFR facilitate JEV infection in hBMECs? It has been widely reported that EGFR participates in the regulation of host innate immunity during viral infection (Lupberger et al, 2013 ; Qiu et al, 2020 ; Wang et al, 2021 ). For example, respiratory virus (RSV) induced EGFR phosphorylation, which inhibited interferon regulatory factor 1 (IRF1)-regulate interferon-lambda (IFN-λ) production and breakdown of airway epithelium antiviral response (Kalinowski et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since EGFR does not affect JEV attachment and entry in hBMECs, how does EGFR facilitate JEV infection in hBMECs? It has been widely reported that EGFR participates in the regulation of host innate immunity during viral infection (Lupberger et al, 2013 ; Qiu et al, 2020 ; Wang et al, 2021 ). For example, respiratory virus (RSV) induced EGFR phosphorylation, which inhibited interferon regulatory factor 1 (IRF1)-regulate interferon-lambda (IFN-λ) production and breakdown of airway epithelium antiviral response (Kalinowski et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two main signalling pathways enriched by the host gene set in the second positive module included G protein-coupled receptors and epidermal growth factor receptors (EGFR). These are involved in the pathogen pathophysiological processes (78, 79) and in mediating cellular entry of numerous pathogen cells (48), respectively. Generally, the functions related to this module have a role in immune pathogenesis by activities of innate and adaptive immune systems.…”
Section: Resultsmentioning
confidence: 99%
“…This process can stimulate the response of the innate immune system (47). GO enrichment analysis has shown that 380 genes across host clusters were enriched with functions which play essential roles in mediating cellular entry of pathogens ( e.g ., epidermal growth factor receptor (EGFR) signalling pathway (48), growth hormone receptor signalling pathway (49), mitochondrial ATP synthesis coupled electron transport (50), protein targeting to endoplasmic reticulum(51)), communication of bacteria with the host environment ( e.g ., positive regulation of establishment of protein localization(52)), control of infection ( e.g ., regulation of protein metabolic process(53)), invading pathogen ( e.g ., response to laminar fluid shear stress (54)), and co-opting host factors ( e.g ., viral gene expression (55)) that can be considered as potential targets in designing antibacterial therapies. Enriched functions were mostly observed at 24h and 4h pi in the host and pathogen, respectively, with mainly downregulated expression (Supplementary Table).…”
Section: Resultsmentioning
confidence: 99%
“…GO enrichment analysis has shown that 380 genes across host clusters were enriched with functions that play essential roles in mediating cellular entry of pathogens (e.g . epidermal growth factor receptor (EGFR) signalling pathway [ 46 ], growth hormone receptor signalling pathway [ 47 ], mitochondrial ATP synthesis coupled electron transport [ 48 ], protein targeting to the endoplasmic reticulum [ 49 ]), communication of bacteria with the host environment (e.g . positive regulation of establishment of protein localisation [ 50 ]), control of infection (e.g .…”
Section: Resultsmentioning
confidence: 99%